Composition of Ions and Trace Metals in Rainwater in Bandung City, Indonesia - Hasan, Nia Yuniarti; Driejana, Driejana; Sulaeman, Aminudin (IPTEK Journal of Proceedings Series, 2017)
The basin shape of Bandung limits dispersion and transport of air pollutants. This topographical characteristic causes air pollutants to be trapped and accumulated within the basin, where urban areas  were located. In the issue of of sustainable city, rainwater could be potential sources of  fresh water. However, air pollution in urban area might alter the natural rainwater composition. Characterization of rainwater was  conducted by collecting rainwater bulk samples at 4 (four) sites located in a transect from high elevation to the lowest at the base of the Bandung basin. Identification of trace metals, cations and anions were performed in rainwater collected in Bandung City during rainy seasons in February to March 2016. Acidity (pH), conductivity, anions and cations (SO42-, NO3-, Cl-, Ca2+, Mg2+, Na+, K+ and NH4+) and trace metals of Ag, Al, As, Ba, Cd, Co, Cr, Cu, Fe, Ni, Pb, Sb, Se, Sn, Sr and Zn were analysed. During the sampling period,  the rainfall rate ranged between 19.02 mm/week to 130.48 mm/week. The results show that rainwater pH were 4.10 – 5.95. The dominant chemical composition of rainwater were sulfat (37% – 39%) and ammonium (17% - 26%), followed by nitrate. The trace metals analyses indicated that lead (Pb) had the highest concentration (mean = 76.68 µg/L). The concentration of the trace metals decreased in order of Pb, Fe, Zn, Al, Se, Cu, As, Ba, Co, Sr, Ni, Cd, Cr, Sn and Sb. Lead is a toxic compound, resulting from human activities, such as fossil fuel burning, mining and manufacturing. The initial analysis of rainwater composition including heavy metals suggested that rainwater contain various and potential harmful substances, including heavy metals. These findings are particularly important  and should be taken into consideration in the context of  rainwater as a water sources in urban area, e,g. rainwater harvesting for the domestic purposes and urban farming.